Kualitas Pelayanan Penyuluhan Pertanian dan Kepuasan Petani dalam Pengembangan Usahatani (Kasus di Desa Sukadamai Kecamatan Dramaga Kabupaten Bogor) - Tahitu, Melvis E (Jurnal Penyuluhan, 2015)
Agricultural extension has significance in changing the behavior of farmers into a better, but the it will be able to realize the goal of agricultural extension if done well and qualified. This study aims to assess the quality of agricultural extension in Sukadamai Village and its relationship with satisfaction and capacity of farmers. The study was designed as a research survey with 38 respondents taking with simple random sampling from 50 farmers in the Sukadamai. Data analysis was conducted by descriptive statistics to describe the distribution of respondents in each measured variable, whereas inferential statistics are used to see the relationship between the variables, in this case used Spearman Rank Correlation analysis. The results showed that formal education and the length of farming relate to assessment of farmers to agricultural extension methods; farm land area associated with the assessment of farmers to agricultural extension agent appearance; the intensity of the visiting agricultural extension agent, agricultural extension materials and methods associated with assessment of the accuracy of agricultural extension; accuracy of extension and methods related to the ability of farmers to identify potential farms, while farmers’ personal characteristics not related to the capacity of farmers. Keywords: Quality of extension services, farmer satisfaction, the capacity of farmers, farm development